Second Trimester Amniotic Fluid Is Reliably Fern Positive and α1-Microglobulin Positive: Dispelling a Labor Deck Myth - Fogelson, Nicholas S.; Browne, Paul C.; Browne, Stanette; Gregg, Anthony R. (American Journal of Perinatology, 2014)
Objective Many physicians erroneously believe and have propagated the “myth” that a second trimester amniotic fluid sample will not fern. We attempted to redemonstrate ferning and to demonstrate the efficacy of an assay for α1-microglobulin in second trimester amniotic fluid samples.Study Design Amniotic fluid samples were collected from women undergoing routine genetic amniocentesis between 15 and 26 weeks. A total of 97 samples of second trimester amniotic fluid were placed on slides and examined for ferning at 5 and 10 minutes. An α1-microglobulin assay was performed on each sample. Data were recorded and reported.Results Approximately 93% of samples were fern positive at 5 minutes and 100% were fern positive at 10 minutes. All samples were α1-microglobulin positive.Conclusion Pure amniotic fluid is reliably fern and α1-microglobulin positive in the second trimester. Republication of data only available in pre-online sources will benefit physicians and patients.
Keywords: amniotic fluid; ruptured membranes; α1-microglobulin; ferning